Traffic Impact Analysis of an Underpass on the Performance of Nearby Signalized Intersections Using VISSIM - Yosua Purba; M. Ridwan Anas; Ahmad Perwira Mulia; Gina Cynthia Raphita Hasibuan; Johannes Tarigan (Journal La Multiapp, 2026)
Medan City is one of the metropolitan cities with a high level of congestion and population density, resulting in traffic jams, delays, as well as air and noise pollution. This study aims to analyze the performance of intersections on S.M Raja – Halat road, Brigjend Katamso – Mesjid Raya road, and Brigjend Katamso - Pelangi road before and after the operation of the underpass at the Ir.H.Juanda – Brigjend Katamso road intersection using vissim software. Data were obtained from traffic surveys such as vehicle volume surveys, road geometry, traffic signal cycle times, and vehicle speeds. The data obtained from the vissim software simulation results include queue lengths, delays, and level of service at the intersection. For the simulation results at the Ir.H.Juanda – Brigjend Katamso road intersection before the operation of the underpass, the average queue length was 274.3 m and the average delay was 307.38 sec/vehicle, with an average level of service of F (very poor). After the operation of the underpass, the average queue length was 8.38 m and the average delay was 0.96 sec/vehicle, with an average level of service of A (excellent). With a 5-year scenario, the average queue length was 38.53 m and the average delay was 12.34 sec/vehicle, with an average level of service of B (good). Thus, a significant difference is clearly visible between before and after the operation of the underpass, such as the results of queue lengths, delays, and service levels, which have caused new conflicts at the intersections closest to the underpass.